Growing research where economies grow: essays on strategy and international expansion of companies from emerging countries - Conti, Claudio Ramos (2014)
In recent years, emerging countries have assumed an increasingly prominent position in the world economy, as growth has picked up in these countries and slowed in developed economies. Two related phenomena, among others, can be associated with this growth: emerging countries were less affected by the 2008-2009 global economic recession; and they increased their participation in foreign direct investment, both inflows and outflows. This doctoral dissertation contributes to research on firms from emerging countries through four independent papers. The first group of two papers examines firm strategy in recessionary moments and uses Brazil, one of the largest emerging countries, as setting for the investigation. Data were collected through a survey on Brazilian firms referring to the 2008-2009 global recession, and 17 hypotheses were tested using structural equation modeling based on partial least squares. Paper 1 offered an integrative model linking RBV to literatures on entrepreneurship, improvisation, and flexibility to indicate the characteristics and capabilities that allow a firm to have superior performance in recessions. We found that firms that pre-recession have a propensity to recognize opportunities and improvisation capabilities for fast and creative actions have superior performance in recessions. We also found that entrepreneurial orientation and flexibility have indirect effects. Paper 2 built on business cycle literature to study which strategies - pro-cyclical or counter-cyclical – enable superior performance in recessions. We found that while most firms pro-cyclically reduce costs and investments during recessions, a counter-cyclical strategy of investing in opportunities created by changes in the environment enables superior performance. Most successful are firms with a propensity to recognize opportunities, entrepreneurial orientation to invest, and flexibility to efficiently implement these investments. The second group of two papers investigated international expansion of multinational enterprises, particularly the use of distance for their location decisions. Paper 3 proposed a conceptual framework to examine circumstances under which distance is less important for international location decisions, taking the new perspective of economic institutional distance as theoretical foundation. The framework indicated that the general preference for low-distance countries is lower: (1) when the company is state owned, rather than private owned; (2) when its internationalization motives are asset, resource, or efficiency seeking, as opposed to market seeking; and (3) when internationalization occurred after globalization and the advent of new technologies. Paper 4 compared five concurrent perspectives of distance and indicated their suitability to the study of various issues based on industry, ownership, and type, motive, and timing of internationalization. The paper also proposed that distance represents the disadvantages of host countries for international location decisions; as such, it should be used in conjunction with factors that represent host country attractiveness, or advantages as international locations. In conjunction, papers 3 and 4 provided additional, alternative explanations for the mixed empirical results of current research on distance. Moreover, the studies shed light into the discussion of differences between multinational enterprises from emerging countries versus those from advanced countries.